(untitled) (The International Journal for Scientific Research, 2024)
This study aimed to investigate the role of the Social Fund for Development (SFD) in promoting life skills for rural families in Yemen. The study focused on a case study of the rural community of Ans District in Thamar Governorate, specifically the Conditional Cash Transfer Program for Nutrition (CCTPN). The study used a descriptive survey approach and applied a questionnaire to a sample of 150 women beneficiaries of the CCTPN. It was analyzed using the Statistical Package for Social Sciences (SPSS). The study found that the CCTPN had a significant impact on enhancing life skills among the beneficiaries, particularly in the areas of health and nutrition. The study also found that the CCTPN had improved some living conditions that were almost non-existent before the project’s intervention. The study showed many negative aspects that impedes the enhancement of life skills, the most prominent of which is that illiteracy is widespread in the rural community, which is a serious threat and a major obstacle to economic and development that should be given significant attention by the relevant authorities.